Genetic and molecular analysis of chlorambucil-induced germ-line mutations in the mouse. - Rinchik, E M (1990)
Eighteen variants recovered from specific locus mutation rate experiments involving the mutagen chlorambucil were subjected to several genetic and molecular analyses. Most mutations were found to be homozygous lethal. Because lethality is often presumptive evidence for multilocus-deletion events, 10 mutations were analyzed by Southern blot analysis with probes at, or closely linked to, several of the specific locus test markers, namely, albino (c), brown (b), and dilute (d). All eight mutations (two c; three b; two d; and one dilute-short ear [Df(d se)]) that arose in post-spermatogonial germ cells were deleted for DNA sequences. No evidence for deletion of two d-se region probes was obtained for the remaining two d mutations that arose in stem-cell spermatogonia. Six of the primary mutants also produced low litter sizes ("semisterility"). Karyotypic analysis has, to date, confirmed the presence of reciprocal translocations in four of the six. The high frequency of deletions and translocations among the mutations induced in post-spermatogonial stages by chlorambucil, combined with its overall high efficiency in inducing mutations in these stages, should make chlorambucil mutagenesis useful for generating experimentally valuable germ-line deletions throughout the mouse genome.